Racism and law in contemporary literature: Space for speaking and concrete of citizenship (Revista Direito em Debate, 2022)
Racist practices and manifestations were conceived and normalized throughout Brazilian history, with repercussions even in the cultural sphere, being present in music, audiovisual productions and also in Literature. This study seeks to deepen the relationship between racism and law in contemporary Literature, envisioning spaces for literary plurality and for the inclusion of black authors in the Information Society, reflecting the focus of the contemporary context for the concretization of citizenship from the perspective decolonial. A bibliographic research was carried out that counted on the contributions and other authors on the theme, achieving results that demonstrated the historical constitution of racist discourses in Literature and envisioning new ways to face this problem in contemporary Literature.